IL-2/CD40-activated macrophages rescue age and tumor-induced T cell dysfunction in elderly mice - Jackaman, Connie; Dye, Danielle; Nelson, Delia (Springer Netherlands, 2014)
The role of macrophages and their interactions with T cells during aging is not well understood. We determined if activating elderly-derived macrophages could rescue age-related and tumor-induced T cell dysfunction. Healthy elderly (18–24 months) Balb/c contained significantly more splenic IL-10-secreting M2-macrophages and myeloid-derived suppressor cells than young (6–8 weeks) mice. Exposure to syngeneic mesothelioma or lung carcinoma-conditioned media polarized peritoneal macrophages into suppressive M2-macrophages regardless of age. Tumor-exposed, elderly, but not young-derived, macrophages produced high levels of IL-4 and could not induce T cell IFN-γ production. We attempted to rescue tumor-exposed macrophages with LPS/IFN-γ (M1 stimulus) or IL-2/agonist anti-CD40 antibody. Tumor-exposed, M1-stimulated macrophages retained high CD40 expression, yet TNF-α and IFN-γ production were diminished relative to non-tumor-exposed, M1-stimulated controls. These macrophages induced young and elderly-derived T cell proliferation however, T cells did not secrete IFN-γ. In contrast, tumor-exposed, IL-2/CD40-stimulated macrophages rescued elderly-derived T cell IFN-γ production, suggesting that IL-2/CD40-activated macrophages could rescue T cell immunity in aging hosts.